Cannabis use as a risk factor for causing motor vehicle crashes: a prospective study. (3rd July 2019) - Brubacher, Jeffrey R.; Chan, Herbert; Erdelyi, Shannon; Macdonald, Scott; Asbridge, Mark; Mann, Robert E.; Eppler, Jeffrey; Lund, Adam; MacPherson, Andrew; Martz, Walter; Schreiber, William E.; Brant, Rollin; et al.
Abstract: Aim: We conducted a responsibility analysis to determine whether drivers injured in motor vehicle collisions who test positive for Δ‐9‐tetrahydrocannabinol (THC) or other drugs are more likely to have contributed to the crash than those who test negative. Design: Prospective case–control study. Setting: Trauma centres in British Columbia, Canada. Participants: Injured drivers who required blood tests for clinical purposes following a motor vehicle collision. Measurements: Excess whole blood remaining after clinical use was obtained and broad‐spectrum toxicology testing performed. The analysis quantified alcohol and THC and gave semiquantitative levels of other impairing drugs and medications. Police crash reports were analysed to determine which drivers contributed to the crash (responsible) and which were 'innocently involved' (non‐responsible). We used unconditional logistic regression to determine the likelihood (odds ratio: OR) of crash responsibility in drivers with 0 < THC < 2 ng/ml, 2 ng/ml ≤ THC < 5 ng/ml and THC ≥ 5 ng/ml (all versus THC = 0 ng/ml). Risk estimates were adjusted for age, sex and presence of other impairing substances. Findings: We obtained toxicology results on 3005 injured drivers and police reports on 2318. Alcohol was detected in 14.4% of drivers, THC in 8.3%, other drugs in 8.9% and sedating medications in 19.8%. There was no increased risk of crash responsibility in drivers with THC < 2 ng/ml or 2 ≤ THC < 5 ng/ml. In drivers with THC ≥ 5 ng/ml, the adjusted OR was 1.74 [95% confidence interval (CI) = 0.59–6.36; P  = 0.35]. There was significantly increased risk of crash responsibility in drivers with blood alcohol concentration (BAC) ≥ 0.08% (OR = 6.00;95% CI = 3.87–9.75; P  < 0.01), other recreational drugs detected (OR = 1.82;95% CI = 1.21–2.80; P  < 0.01) or sedating medications detected (OR = 1.45; 95%CI = 1.11–1.91; P  < 0.01). Conclusions: In this sample of non‐fatally injured motor vehicle drivers in British Columbia, Canada, there was no evidence of increased crash risk in drivers with Δ‐9‐tetrahydrocannabinol < 5 ng/ml and a statistically non‐significant increased risk of crash responsibility (odds ratio = 1.74) in drivers with Δ‐9‐tetrahydrocannabinol ≥ 5 ng/ml.